PV integrated series active filter for sag voltage and harmonic compensation - Abdelmalek Meftouhi; Othmane Abdelkhalek; Ahmed Allali; Abdallah Ben Abdelkader; Toufik Toumi (Institute of Advanced Engineering and Science, 2019)
The use of loads in the past few days is becoming vast, giving an alarm signal to the power system and electronics engineers in terms of power quality. Due to the large amount of non-linear power electronics, utilities frequently experience voltage and harmonic distortions every day. In this paper, the combination of the Series active power filter SAPF with a PV source is deliberated. The PV based on the SAPF aims to compensate voltage deviations or disturbances that occur in the system caused by power quality issues. The proposed system consists of a PV source connected to the DC link through two dc-dc converters, the first extracts the maximum power of the PV source through pulse with modulation PWM signals generated from the maximum power point tracker MPPT controller. Thus, the second converter is used to regulate the high voltage side of the converter through closed control loops using Fuzzy Logic Controller FLC, in addition to a voltage source inverter VSI and a series injection transformer. Despite of fluctuations of the DC link during the compensation of the needed energy, MPPT and closed control loops generate PWM signals to the switching devices of dc-dc boost converters in order to extract maximum PV power and to maintain the bus voltage within its limits and around its reference values respectively. The proposed topology is simulated in Matlab Simulink software, where simulation results show that the proposed PV based SAPF can efficiently reduce problems of voltage sag and harmonic.